Establishment of a synthetic ECV model and its prognostic value in diabetes patients with acute myocardial infarction - Chen, Lei; Qiu, Bowen; Du, Xinjia; Liu, Jiahua; Lu, Yuan; Che, Wenliang; Chen, Wensu (Frontiers in Endocrinology, 2025)
BackgroundExtracellular volume (ECV) is an important marker of myocardial fibrosis. However, the prognostic role of ECV in diabetes patients is unknown. In addition, synthetic ECV without blood sampling has not been reported in diabetes cohorts. This study investigated the establishment and validation of synthetic ECV and its prognostic value in type 2 diabetes mellitus (T2DM) patients with acute myocardial infarction (AMI).MethodsThis single-center retrospective study included T2DM patients with AMI who completed cardiac magnetic resonance (CMR) during hospitalization. The patients were randomly divided into a derivation group and a validation group. MACE included all-cause death, recurrent MI, stroke, or heart failure. ECV in integral (Integral ECV), non-myocardial infarction region (NMI-ECV), and myocardial infarction region (MI-ECV) was obtained by CMR.ResultsThe study included 157 patients, with a median time from admission to CMR of 4 days. Bland-Altman and Pearson analysis showed good consistency and correlation between conventional ECV and synthetic ECV. Cox regression showed that Integral ECV (HR=1.07; 95%CI: 1.01 ~ 1.13, p = 0.023), MI-ECV (HR=1.03; 95%CI: 1.00 ~ 1.07, p = 0.024), and NMI-ECV (HR=1.07; 95%CI: 1.00 ~ 1.14, p = 0.039) were independently associated with MACE in different models. Kaplan-Meier analysis indicated that patients with a high synthetic ECV had a significantly higher MACE risk.ConclusionsSynthetic ECV is strongly consistent and correlated with conventional ECV in T2DM patients with AMI. Elevated synthetic ECV is an independent risk factor for MACE in T2DM patients with AMI.